BIMBINGAN KONSELING ISLAM SEBAGAI SOLUSI DALAM MENGATASI KENAKALAN REMAJA - Supiyah Surya Ayuning Setya; Nauval Awalludin; Salsa Mulyana Sari (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2025)
Juvenile delinquency is a complex social phenomenon with significant impacts in the modern era. This research aims to explore the effectiveness of Islamic counseling guidance as a solution in overcoming juvenile delinquency, focusing on the integration of spiritual and moral values. Using a qualitative research method with a literature-based descriptive-interpretative approach, data were analyzed from various relevant literature sources. The results show that Islamic counseling guidance is able to help adolescents in knowing themselves, understanding their potential, and developing faith and piety. This process not only resolves the problem of deviant behavior, but also fosters higher moral awareness. The values of the Qur'an and Hadith serve as a foundation in providing holistic solutions, which are relevant to preventing negative behaviors such as brawls, drug abuse, and promiscuity. The conclusion of the study confirms that the Islamic counseling guidance approach is effective in shaping the character of responsible and noble adolescents, so that it can contribute to reducing the level of juvenile delinquency. This study provides recommendations for the development of a more systematic and sustainable faith-based counseling guidance program. Keywords: guindance, counseling, juvenile delinquency.